Zirconia powder and its production method

JP2025022983AActive Publication Date: 2025-02-14TOSOH CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024205286
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
2039-10-03

AI Technical Summary

Benefits of technology

【0008】 本開示によって、低温で焼結した場合であっても高い導電率を示すジルコニア焼結体を与えるジルコニア粉末及びその製造方法、並びに、当該ジルコニア粉末により得られるジルコニア焼結体、その製造方法及びこれを用いた固体電解質、の少なくとも1つを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022983000001
    Figure 2025022983000001
  • Figure 2025022983000002
    Figure 2025022983000002
Patent Text Reader

Abstract

To provide at least one of the following: a zirconia powder which gives a zirconia sintered body exhibiting high electrical conductivity even when sintered at a low temperature and a method for producing the zirconia powder; and a zirconia sintered body obtained from the zirconia powder, a method for producing the zirconia sintered body, and a solid electrolyte using the same.SOLUTION: A zirconia powder comprises one or more stabilizers selected from the group of yttria, calcia, magnesia, and ceria, in which a proportion of monoclinic crystals in a crystal phase is 0.5% or less, an average particle diameter is less than 0.5 μm, and a proportion of particles of 1 μm or less in volume particle size distribution is 100%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a zirconia powder, and in particular to a zirconia powder that provides a zirconia sintered body suitable for solid electrolytes. [Background technology]

[0002] Zirconia-based solid electrolytes are used in solid oxide fuel cells (SOFCs) and the like. For example, Patent Document 1 reports a solid electrolyte obtained by crushing a zirconia sintered body containing yttria (Y2O3) and ceria (CeO2), mixing this with a lanthanide oxide, manganese dioxide, and iron oxide, and sintering the mixture at 1450°C. Patent Document 2 discloses a solid electrolyte integrated with a solid electrolyte layer made of zirconia containing 8 mol% or 10 mol% yttria and a fuel electrode obtained by co-sintering a compact having a fuel electrode and a barrier layer at 1400°C. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2012 / 105580 [Patent Document 2] Patent No. 5770400 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] The zirconia-based solid electrolytes of Patent Documents 1 and 2 both require a high sintering temperature of 1400° C. or higher to exhibit practical electrical conductivity.

[0005] In response to this, the present disclosure has an object to provide at least one of a zirconia powder that gives a zirconia sintered body that exhibits high electrical conductivity even when sintered at a low temperature, a method for producing the same, and a zirconia sintered body obtained from the zirconia powder, a method for producing the same, and a solid electrolyte using the same. [Means for solving the problem]

[0006] The gist of the present disclosure is as follows. [1] A zirconia powder comprising one or more stabilizers selected from the group consisting of yttria, calcia, magnesia and ceria, wherein the proportion of monoclinic crystals in the crystal phase is 0.5% or less, the average particle size is less than 0.5 μm, and the proportion of particles with a size of 1 μm or less in the volumetric particle size distribution is 100%. [2] The zirconia powder according to the above [1], in which the proportion of particles having a size of 0.2 μm or less in the volume particle size distribution is 10% to 90%. [3] The zirconia powder according to the above [1] or [2], which has a particle size peak having a top at 0.3 to 0.5 μm in a volume particle size distribution. [4] The zirconia powder according to any one of [1] to [3], wherein the content of the stabilizer is more than 4 mol% and not more than 12 mol%. [5] The zirconia powder according to any one of [1] to {4} above, which is a compound containing at least one of a cation having an ionic radius smaller than that of a zirconium ion and a cation having a valence other than tetravalent. [6] The zirconia powder according to the above [5], wherein the compound contains one or more cations selected from the group consisting of aluminum, silicon and germanium. [7] The zirconia powder according to [5] or [6] above, wherein the content of the compound is greater than 0 mass% and not more than 1 mass%. [8] Average granule particle size is 30 μm or more and 80 μm or less, and the light bulk density is 1.00 g / cm 3 More than 1.40g / cm 3 The zirconia powder according to any one of the above items [1] to [7] below.

[0007] [9] A method for producing a zirconia powder according to any one of [1] to [8] above, comprising the steps of: mixing a zirconia sol having an amount of zirconium element calculated by the following formula of 2 mass% or less with one or more compounds selected from the group consisting of yttrium, calcium, magnesium and cerium; and treating the zirconia sol at a calcination temperature of 900°C or more and 1200°C or less. W Zr =(m / m0)×100 In the above formula, W Zr is the amount of adsorbed zirconium (mass%). m is the mass (mg) of zirconium in the filtrate obtained by ultrafiltration of a slurry in which zirconia sol is dispersed in pure water, using an ultrafiltration membrane with a molecular weight cutoff of 500 to 3 million, converted into zirconia (ZrO2). m o is the mass (mg) of the zirconia sol before ultrafiltration after heat treatment at 1000°C for 1 hour in air.

[10] A method for producing a zirconia sintered body, comprising using the zirconia powder according to any one of [1] to [8] above.

[11] A ceramic ceramic material containing one or more stabilizers selected from the group consisting of yttria, calcia, magnesia, and ceria, and having a conductivity of 5.0×10 at 600°C. -3 A zirconia sintered body characterized by a viscosity of 10 ...

[12] A solid electrolyte comprising the zirconia sintered body according to

[11] above. Effect of the Invention

[0008] The present disclosure can provide at least one of a zirconia powder that gives a zirconia sintered body that exhibits high electrical conductivity even when sintered at a low temperature, a method for producing the same, and a zirconia sintered body obtained from the zirconia powder, a method for producing the same, and a solid electrolyte using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the zirconia powder of the present disclosure will be described with reference to an example embodiment.

[0010] The "average particle size" is the particle size (median size) corresponding to a volume ratio of 50% on the cumulative volume particle size distribution curve obtained by volume particle size distribution measurement using a laser diffraction method.

[0011] The "crystallite size" refers to the value calculated from the Bragg angle (θ) of the diffraction line measured by powder X-ray diffraction (XRD) and the half-width (β) of the diffraction line corrected for mechanical broadening, using the following formula 3: Dx = κλ / (β cosθ) In the above formula, κ is the Scherrer constant (κ=1), λ is the measurement wavelength, and β is The crystallite size of the zirconia fine powder is determined from the diffraction line with the strongest intensity.

[0012] The "BET specific surface area" is a value determined by the BET one-point method in accordance with JIS R 1626-1996, using nitrogen (N2) as the adsorbed substance.

[0013] The "stabilizer content" is the molar ratio of the stabilizer to zirconia and the stabilizer calculated as an oxide.

[0014] The "monoclinic fraction of the crystalline phase" (hereinafter also referred to as the "monoclinic fraction") is the fraction of the crystalline phase of zirconia that is monoclinic. For powders, the powder X-ray diffraction (hereinafter also referred to as "XRD") pattern is used, while for sintered bodies, the XRD pattern of the surface of the sintered body after mirror polishing is used, and it can be calculated from the following formula.

[0015] f m ={I m (111)+I m (11-1)} / [I m (111) +I m (11-1)+I t (111)+I c (111)] × 100

[0016] In the above formula, f m is the monoclinic fraction (%), I m(111) and I m (11-1) are the area intensities of the XRD peaks corresponding to the monoclinic (111) and (11-1) planes, respectively, and I t (111) is the area intensity of the XRD peak corresponding to the (111) plane of the tetragonal crystal, and I c (111) is the integrated intensity of the XRD peak corresponding to the (111) plane of the cubic crystal.

[0017] The conditions for measuring the XRD pattern are as follows: Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33°

[0018] In the above-mentioned XRD pattern measurement, preferably, the XRD peaks corresponding to the respective crystal planes of zirconia are measured as peaks having peak tops at the following 2θ angles.

[0019] XRD peak corresponding to the monoclinic (111) plane: 2θ=31±0.5° XRD peak corresponding to the monoclinic (11-1) plane: 2θ=28±0.5° The RD peaks corresponding to the (111) planes of the tetragonal and cubic crystals were measured in duplicate, and their 2θ was 2θ=30±0.5°.

[0020] The integrated intensity of the XRD peak of each crystal plane can be determined by separating each XRD peak using the calculation program "PRO-FIT" according to the method described in H. Toraya, J. Appl. Crystallogr., 19, 440-447 (1986).

[0021] The "ionic radius" is a value described in Acta. Crystallogr., A32, 751-67 (1976) (hereinafter also referred to as "reference literature").

[0022] "Additive content" refers to the ratio of additive / (ZrO2 + stabilizer + additive) expressed as mass %, where the additive is expressed as an oxide equivalent.

[0023] The "average sol particle size" is the sol size (median size) corresponding to a volume ratio of 50% on a cumulative volume particle size distribution curve obtained by dynamic light scattering particle size distribution measurement.

[0024] The "actual density of the sintered body" can be measured using the Archimedes method.

[0025] The zirconia powder of the present embodiment contains one or more stabilizers selected from the group consisting of yttria, calcia, magnesia, and ceria. The stabilizer is preferably at least one of yttria and ceria. It is more preferable that the stabilizer is yttria, since this produces a zirconia sintered body having properties suitable for a solid electrolyte.

[0026] The type and content of the stabilizer may be appropriately changed depending on the properties of the desired zirconia sintered body. For example, when the stabilizer is yttria, the content of yttria is preferably more than 4 mol% and not more than 12 mol%, and more preferably 6 mol% or more and not more than 10 mol%.

[0027] The zirconia powder of this embodiment has a ratio of monoclinic crystals in the crystal phase (hereinafter also referred to as the "monoclinic phase ratio") of 0.5% or less, and preferably 0% to 0.2%. If the monoclinic phase ratio exceeds this range, the sintering temperature required for densification becomes high, and even if densification progresses, coarse pores are likely to remain. If the monoclinic phase ratio is 0.5% or less, the other crystal phases are arbitrary, and include tetragonal and cubic crystals, and preferably cubic crystals. The crystal phase of the zirconia powder of this embodiment is preferably composed of cubic crystals and monoclinic crystals.

[0028] The zirconia powder of this embodiment has an average particle size of less than 0.5 μm. Outside this range of average particle size, the amount of hard and coarse aggregated particles increases, and the moldability and sinterability of the zirconia powder decreases. Since the moldability and sinterability tend to be high, the average particle size is preferably 0.05 μm or more and 0.4 μm or less, more preferably 0.05 μm or more and 0.35 μm or less, and even more preferably 0.1 μm or more and 0.3 μm or less.

[0029] For the same reason, the zirconia powder of this embodiment is a powder in which the proportion of particles of 1 μm or less in the volume particle size distribution (hereinafter also referred to as the "particle ratio") is 100%, and does not contain particles exceeding 1 μm in the volume particle size distribution. Therefore, the zirconia powder of this embodiment can also be regarded as a fine zirconia powder.

[0030] Since there is a tendency for moldability to be improved, the zirconia powder of this embodiment preferably has a ratio of particles of 0.2 μm or less in the volume particle size distribution (hereinafter also referred to as the "microparticle ratio") of 10% or more and 90% or less, more preferably 20% or more and 80% or less, and even more preferably 30% or more and 70% or less.

[0031] Since a dense sintered body can be easily obtained even at a lower sintering temperature, the zirconia powder of the present embodiment preferably has a particle size peak with a top at 0.3 to 0.5 μm in the volumetric particle size distribution, and the width of the particle size peak is preferably 0.05 μm or more and 0.2 μm or less.

[0032] The particle ratio and fine particle ratio are the ratios of particles of each particle size to a cumulative value of 100% in a cumulative volume particle size distribution curve obtained by volume particle size distribution measurement by laser diffraction method, and the particle size peak is the peak in the particle size distribution obtained by volume particle size distribution measurement by laser diffraction method.

[0033] Other physical properties of the zirconia powder of this embodiment are optional, but for example, the BET specific surface area is preferably 11 m 2 / g or more 20m 2 / g or less, more preferably 13m 2 / g or more 19m 2 / g or less, and the average crystallite size is 26 nm or more and 50 nm or less, preferably 30 nm or more and 45 nm or less, and more preferably 35 nm or more and 40 nm or less.

[0034] The zirconia powder of this embodiment may contain a stabilizer with the remainder being zirconia, but since the sinterability can be improved by accelerating the densification rate, the zirconia powder of this embodiment preferably contains a compound (hereinafter also referred to as "additive") containing at least one of a cation having an ionic radius smaller than that of a zirconium ion and a cation having a valence other than 4. This makes it easier to obtain a zirconia sintered body with high density even at a lower sintering temperature. The additive is preferably a compound containing one or more cations selected from the group of aluminum, silicon, and germanium, more preferably a compound containing at least one cation of aluminum and germanium, and even more preferably a compound containing aluminum cations and germanium cations. Specific examples of the additive include at least one selected from the group of alumina (Al2O3), silica (SiO2), and germania (Ge2O3), preferably at least one of alumina and germania. The zirconia powder of this embodiment preferably does not contain a cation having an ionic radius equal to or larger than that of a zirconium ion and a valence of 4.

[0035] In the reference, the zirconium cation has an ionic radius of 0.86 Å and a valence of 4, the aluminum cation has an ionic radius of 0.68 Å and a valence of 3, the silicon cation has an ionic radius of 0.54 Å and a valence of 4, and the germanium cation has an ionic radius of 0.67 Å and a valence of 4.

[0036] The content of the additive can be, for example, 0 mass% or more and 1 mass% or less, calculated as the mass ratio of the additive in terms of oxide relative to the mass of the zirconia powder. When the additive is contained, the content can be, for example, more than 0 mass% and 1 mass% or less, or even 0.05 mass% or more and 0.8 mass% or less.

[0037] The zirconia powder of this embodiment may be a slowly agglomerated particle, so-called granule. When the zirconia powder of this embodiment is a granule, the average granule particle size is 30 μm or more and 80 μm or less, and the bulk density is 1.10 g / cm 3 More than 1.40g / cm 3 The following can be exemplified.

[0038] The zirconia powder of the present embodiment is preferably provided as a zirconia powder for a solid electrolyte for obtaining a zirconia sintered body for a solid electrolyte.

[0039] The zirconia powder of the present embodiment can be obtained by a production method characterized by comprising a step of mixing a zirconia sol having an amount of zirconium element calculated by the following formula of 2 mass% or less with one or more compounds selected from the group consisting of yttrium, calcium, magnesium, and cerium. W Zr =(m / m0)×100

[0040] In the above formula, W Zr is the amount of adsorbed zirconium (mass%). m is the mass (mg) of zirconium in the filtrate obtained by ultrafiltration of a slurry in which zirconia sol is dispersed in pure water, using an ultrafiltration membrane with a molecular weight cutoff of 500 to 3 million, converted into zirconia (ZrO2). m o is the mass (mg) of the zirconia sol before ultrafiltration after heat treatment at 1000°C for 1 hour in air. The amount of zirconium in the filtrate can be measured by ICP analysis.

[0041] The zirconia sol subjected to the step of mixing the zirconia sol with a compound such as yttrium (hereinafter also referred to as the "mixing step") has an amount of zirconium element calculated by the following formula (hereinafter also referred to as the "adsorbed zirconium amount") of 2 mass% or less, preferably 0 mass% or more and 1 mass% or less, more preferably 0 mass% or more and 0.5 mass% or less, and even more preferably 0 mass% or more and 0.01 mass% or less. WZr =(m / m0)×100

[0042] In the above formula, W Zr is the amount of adsorbed zirconium (mass%). m is the mass (mg) of the amount of zirconium in the filtrate obtained by ultrafiltration of a slurry in which zirconia sol is dispersed in pure water, using an ultrafiltration membrane with a molecular weight cutoff of 500 to 3 million, converted into zirconia (ZrO2). The amount of zirconium in the filtrate can be measured by ICP analysis. m o m and m are the mass (mg) of the zirconia sol before ultrafiltration after heat treatment at 1000°C for 1 hour in air. o The measurements of can be carried out by preparing the same amount of zirconia sol before ultrafiltration.

[0043] If the amount of adsorbed zirconium exceeds 2 mass %, the powder particles are strongly sintered together during calcination, resulting in an increase in coarse particles including hard agglomerates, which results in poor compactibility and sinterability.

[0044] In order to improve moldability, the average sol particle size of the zirconia sol is preferably 0.05 μm or more and 0.2 μm or less.

[0045] The zirconia sol may be produced by any method as long as it has the above-mentioned characteristics. The production method of the zirconia sol can be exemplified by at least one of a hydrothermal synthesis method and a hydrolysis method. In the hydrothermal synthesis method, a coprecipitate obtained by mixing a zirconium salt with an alkali or the like in the presence of a solvent is heat-treated at 100 to 200°C to obtain a zirconia sol. In the hydrolysis method, the zirconium salt is heated in the presence of a solvent to hydrolyze the zirconium salt, thereby obtaining a zirconia sol. Thus, the zirconia sol can be exemplified as a zirconia sol obtained by a hydrothermal synthesis method or a hydrolysis method, and a zirconia sol obtained by a hydrolysis method is preferable.

[0046] In addition, when obtaining zirconia sol by hydrolysis, it is preferable to control the pH at the end of the reaction. This makes it easier to control the average sol particle size of the zirconia sol. For example, in order to obtain a hydrated zirconia sol with an average sol particle size of 0.05 to 0.2 μm, it is preferable to make the pH at the end of the reaction at least either acidic or basic, specifically at least either 0.3 to 0.6 or 0.8 to 1.4.

[0047] The zirconium salt used in the production of the zirconia sol may be one or more selected from the group consisting of zirconium oxychloride, zirconyl nitrate, zirconium chloride, and zirconium sulfate, with at least one of zirconium chloride and zirconium oxychloride being preferred, and zirconium oxychloride being more preferred. In another embodiment, the zirconium salt may be a mixture of zirconium hydroxide and an acid. The acid may be at least one of an inorganic acid and an organic acid, with at least one selected from the group consisting of acetic acid, citric acid, hydrochloric acid, nitric acid, and sulfuric acid being preferred, and at least one selected from the group consisting of hydrochloric acid, nitric acid, and sulfuric acid being more preferred.

[0048] The alkali used for producing the zirconia sol can be one or more selected from the group consisting of ammonia, sodium hydroxide, and potassium hydroxide. In another embodiment, the alkali is a compound that decomposes to exhibit basicity, such as urea.

[0049] The one or more compounds selected from the group consisting of yttrium, calcium, magnesium, and cerium (hereinafter also referred to as "stabilizer source") used in the manufacturing method of this embodiment can be exemplified by one or more selected from the group consisting of chlorides, fluorides, nitrates, carbonates, sulfates, acetates, oxides, and hydroxides containing one or more selected from the group consisting of yttrium, calcium, magnesium, and cerium, and is preferably one or more selected from the group consisting of chlorides, fluorides, oxides, and hydroxides, and more preferably at least one of chlorides and oxides.

[0050] The zirconia sol and the stabilizer source may be mixed uniformly by any method, for example, by adding the stabilizer source to an aqueous solution of the zirconia sol.

[0051] The concentration of the stabilizer source to be mixed with the zirconia sol may be adjusted so that the stabilizer source, calculated as an oxide relative to the zirconia in the zirconia sol, is the desired stabilizer content in the zirconia powder. For example, when the stabilizer source is an yttria source, the stabilizer source may be more than 4 mol% and 12 mol% or less, preferably 6 mol% or more and 10 mol% or less.

[0052] The manufacturing method of this embodiment preferably includes a step of drying the zirconia sol after mixing with the stabilizer source (hereinafter, also referred to as a "drying step"). The drying method may be any method capable of removing the solvent, hydration water of the zirconia sol, and adsorbed water, and may be, for example, a treatment in the air at 120 to 200°C.

[0053] The manufacturing method of this embodiment includes a step of treating the zirconia sol at a calcination temperature of 900°C or higher and 1200°C or lower (hereinafter also referred to as the "calcination step"), whereby the zirconia powder of this embodiment is obtained. When the calcination temperature is within this range, the zirconia powder particles do not strongly aggregate with each other, or strongly aggregated coarse particles are unlikely to be generated. This makes it easier to control the average particle size of the zirconia powder of this embodiment by pulverization or the like. Preferable calcination conditions include 900°C or higher and 1100°C or lower.

[0054] When producing a zirconia powder containing an additive, the additive may be mixed into the zirconia sol in at least one of the mixing step and the calcination step. Any additive may be mixed with the zirconia sol, and examples of the additive include one or more selected from the group consisting of alumina, hydrated alumina, alumina sol, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate, silica, silica sol, silicic acid, germanium oxide, and germanium hydroxide. The additive is preferably one or more selected from the group consisting of alumina, hydrated alumina, alumina sol, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate, germanium oxide, and germanium hydroxide, more preferably one or more selected from the group consisting of alumina, hydrated alumina, alumina sol, germanium oxide, and germanium hydroxide, and even more preferably at least one of alumina and germanium oxide.

[0055] In order to obtain the average particle size and particle size ratio of the zirconia powder of this embodiment, a step of pulverizing the zirconia powder (hereinafter also referred to as a "pulverizing step") may be included. The pulverization method may be either dry pulverization or wet pulverization, and wet pulverization is preferable. A particularly preferred pulverization method is wet pulverization using zirconia balls as a pulverization medium, preferably zirconia balls having a diameter of 3 mm or less, more preferably zirconia balls having a diameter of 2 mm or less. A specific example of wet pulverization is pulverization using one or more selected from the group consisting of a vibration mill, a continuous media stirring mill, and a ball mill.

[0056] In the manufacturing method of this embodiment, when the zirconia powder is to be granulated, it can be granulated by a known method, for example, spray granulation.

[0057] The zirconia powder of this embodiment can be used in a method for producing a sintered body using the zirconia powder of this embodiment. The method for producing a sintered body using the zirconia powder of this embodiment is arbitrary, and examples thereof include a method of molding the zirconia powder of this embodiment and sintering the obtained molded body, and a method of molding the zirconia powder of this embodiment, calcining the obtained molded body, and sintering the obtained calcined body.

[0058] The molding method may be any method, and may be at least one selected from the group consisting of die press molding, sheet molding, doctor blade method, calendar roll method, injection molding, and cold isostatic pressing (CIP). Specific molding methods include, for example, die press molding at 20 MPa to 100 MPa, preferably 30 MPa to 80 MPa, and CIP method at 30 MPa to 250 MPa, preferably 50 MPa to 200 MPa. The zirconia powder used for molding may be zirconia powder or a composition containing zirconia powder.

[0059] The sintering method may be one or more selected from the group consisting of atmospheric sintering, pressure sintering, and vacuum sintering, and at least one of atmospheric sintering and pressure sintering is preferred. Because it is simple, atmospheric sintering is preferred, and atmospheric sintering in an air atmosphere is particularly preferred. Conditions for atmospheric sintering include a sintering temperature of 1200°C to 1600°C, and even more preferably 1250°C to 1500°C, and a sintering time of 1 hour to 24 hours, preferably 2 hours to 20 hours. However, since the zirconia powder of this embodiment can obtain a zirconia sintered body having high conductivity even at a sintering temperature lower than that of the conventional one, the sintering temperature is more preferably 1200°C to 1400°C, and particularly preferably 1200°C to 1325°C.

[0060] The zirconia sintered body obtained from the zirconia powder of this embodiment (hereinafter also referred to as "the zirconia sintered body of this embodiment") contains one or more stabilizers selected from the group consisting of yttria, calcia, magnesia, and ceria. The stabilizer is preferably at least one of yttria and ceria, and more preferably yttria.

[0061] The type and content of the stabilizer may be appropriately changed depending on the properties of the desired zirconia sintered body. For example, when the stabilizer is yttria, the content of yttria is preferably more than 4 mol% and not more than 12 mol%, and more preferably 6 mol% or more and not more than 10 mol%.

[0062] The zirconia sintered body of the present embodiment may contain a stabilizer with the remainder being zirconia, but may contain one or more selected from the group consisting of alumina (Al2O3), silica (SiO2) and germania (Ge2O3), preferably at least one of alumina and germania.

[0063] The zirconia sintered body of this embodiment preferably contains at least cubic crystals in the crystal phase, and has cubic crystals as the main phase, and more preferably has only cubic crystals. This tends to increase the electrical conductivity. In the zirconia sintered body of this embodiment, "having cubic crystals as the main phase" means that the proportion of cubic crystals in the zirconia crystal phase is the highest.

[0064] The zirconia sintered body of this embodiment has a measured density of 5.76 g / cm 3 and preferably 5.82 g / cm 3 More preferably, 5.94 g / cm 3 That's all.

[0065] The upper limit of the measured density is the theoretical density. When the zirconia sintered body of the present embodiment is a sintered body obtained by normal pressure sintering (normal pressure sintered body), the measured density is 6.02 g / cm 3 Below that, 6.01g / cm 3 The following are some of the reasons:

[0066] The zirconia sintered body of the present embodiment has a three-point bending strength of 350 MPa or more, preferably 380 MPa or more, and more preferably 400 MPa or more, measured by a method in accordance with JIS R 1601. When the zirconia sintered body of the present embodiment is a sintered body obtained by normal pressure sintering (normal pressure sintered body), the three-point bending strength is 600 MPa or less, and further 500 MPa or less.

[0067] The zirconia sintered body of the present embodiment preferably has a conductivity suitable for a solid electrolyte, particularly a conductivity suitable for a low-temperature solid electrolyte that operates at temperatures below 800° C. Specifically, the conductivity at 600° C. is 5.0×10 -3 S / cm or more, and 6.5×10 -3 When the zirconia sintered body of the present embodiment is a sintered body obtained by atmospheric sintering (atmospheric sintered body), the electrical conductivity is preferably 1.0×10 -2 S / cm or less.

[0068] The zirconia sintered body of the present embodiment exhibits high electrical conductivity and can therefore be used as a solid electrolyte, and further as a solid electrolyte for solid oxide fuel cells (SOFCs).

[0069] The SOFC including the zirconia sintered body of the present embodiment may be an SOFC including a fuel electrode, an air electrode, and the zirconia sintered body of the present embodiment.

[0070] The fuel electrode may be made of any known material, for example, a Ni-zirconia cermet material made of 60 mass % nickel and 40 mass % zirconia.

[0071] The air electrode may be made of any known material, for example, lanthanum strontium manganate (La(Sr)MnO3).

[0072] The manufacturing method of the SOFC including the zirconia sintered body of this embodiment is arbitrary. For example, a method of applying at least one of the fuel electrode and its precursor compound to one side of the zirconia sintered body of this embodiment, applying at least one of the air electrode and its precursor compound to the other side, and then sintering them as one body can be mentioned. Furthermore, the zirconia powder of this embodiment provides a zirconia sintered body that exhibits high electrical conductivity even at a sintering temperature similar to that of the fuel electrode and the air electrode. Therefore, a SOFC in which the fuel electrode, the solid electrolyte, and the air electrode are integrated can be obtained by one sintering by a method of stacking at least one of the fuel electrode and its precursor compound, the zirconia powder of this embodiment, and at least one of the air electrode and its precursor compound, and molding and sintering them as one body. EXAMPLES

[0073] The present embodiment will be specifically described below with reference to examples, but the present disclosure is not limited to these examples. (average sol particle size) The average sol particle size of the zirconia sol was measured using a dynamic light scattering particle size distribution analyzer (apparatus name: UPA The measurement was performed using a zirconia sol-containing solution (Microtrack-Bell, UT151). As a pretreatment for the sample, the solution containing the zirconia sol was suspended in pure water and dispersed for 3 minutes using an ultrasonic homogenizer. (Amount of adsorbed zirconium) A portion of the slurry containing the hydrolyzed zirconia sol was collected, and half of it was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 5 to 3 million to obtain a filtrate. The remaining half of the slurry was heat-treated at 1000°C for 1 hour in an air atmosphere, and the mass (mg) was obtained. The zirconium content of each was measured by ICP analysis to determine m and m0, The amount of adsorbed zirconium was calculated from the following formula. W Zr =(m / m0)×100

[0074] (Particle size distribution measurement) The volumetric particle size distribution curve and cumulative volumetric particle size distribution curve of the powder sample were obtained using the HRA mode of a Microtrac particle size distribution meter (product name: MT3000II, Microtrac Bell Co., Ltd.), and the average particle size, particle ratio, fine particle ratio, particle size peak, and particle size peak width were measured using the attached analysis software. Prior to the measurement, the powder sample was suspended in pure water and dispersed for 10 minutes using an ultrasonic homogenizer as pretreatment. (Monoclinic phase ratio) A general X-ray diffraction apparatus (product name: Ultima II V, manufactured by Rigaku Corporation) was used to obtain the XRD pattern of the powder sample. The conditions for the XRD measurement were as follows: Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33° The monoclinic fraction was calculated using the obtained XRD pattern and the calculation program "PRO-FIT" according to the above formula.

[0075] (BET specific surface area) The BET specific surface area of ​​the powder sample was measured using a general flow-type automatic specific surface area measurement device (Device name: FlowSorb III2305, Shimadzu Corporation) and nitrogen as the adsorption gas. Prior to the measurement, the powder sample was degassed in air at 250°C for 30 minutes as a pretreatment. (Average granule size) The average particle size of the zirconia granules was determined by a sieving test method. (Molded object density) The mass of the compact sample was measured with a balance, and the volume was measured with a vernier caliper to obtain the dimensions. The actual density was calculated from the obtained mass and volume. (Sintered body density) The actual density of the sintered body sample was measured by the Archimedes method. Prior to the measurement, the mass of the sintered body after drying was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. (Three-point bending strength) The bending strength of the sintered body samples was measured by a three-point bending test in accordance with JIS R 1601. The measurement was performed using a columnar sintered body sample with a support distance of 30 mm, width of 4 mm, and thickness of 3 mm, and the bending strength was calculated by averaging 10 measurements. (conductivity) The electrical conductivity was measured by an AC impedance method using a frequency response analyzer (device name: 1260, manufactured by Solartron) and a potentiostat (device name: 1286A, manufactured by Solartron) as measuring devices. The measurement conditions are shown below. Measurement sample: A rectangular sintered body with dimensions of 4 mm length x 3 mm width x 35 mm length Measurement atmosphere: Air Measurement temperature: 600℃ Measurement method: Four-probe method Electrode terminal: Pt wire (diameter 0.2mm) Distance between voltage terminals: 15mm Measurement frequency: 1MHz~0.1Hz Applied current: 1mA

[0076] Example 1 A 2 mol / L aqueous solution of zirconium oxychloride was mixed with 2 mol / L aqueous ammonia and pure water to obtain an aqueous solution of zirconium oxychloride with a zirconia equivalent concentration of 0.8 mol / L. The aqueous solution was hydrolyzed at boiling temperature for 200 hours while stirring to obtain a zirconia sol. The amount of adsorbed zirconium in the obtained zirconia sol was 0.5 mass% and the average sol particle size was 0.1 μm.

[0077] Yttrium chloride was added to and mixed with the zirconia sol so that the yttria concentration was 8 mol %, and the sol was dried at 160° C. in air, and then calcined at 980° C. for 2 hours in air to obtain zirconia powder.

[0078] The obtained zirconia powder was washed with a sufficient amount of pure water, and then made into a slurry, which was then pulverized for 24 hours in a vibration mill equipped with zirconia balls having a diameter of 2 mm as a pulverizing medium. After pulverization, the zirconia powder was dried in the air at 130° C. to obtain the zirconia powder of this example.

[0079] The zirconia powder of this embodiment was molded under a pressure of 70 MPa, and then sintered under atmospheric pressure at 1300° C. for 2 hours to obtain a zirconia sintered body of this example.

[0080] Example 2 The zirconia powder of this example was obtained under the same conditions as in Example 1, except that after washing with pure water, alumina sol was added to the zirconia powder so that the alumina content was 0.25 mass %.

[0081] The zirconia sintered body of this example was obtained in the same manner as in Example 1, except that the sintering temperature was 1250°C.

[0082] Example 3 After washing with pure water, the zirconia powder of this example was obtained under the same conditions as in Example 1, except that alumina sol was added to the zirconia powder so that the alumina content was 0.25 mass% and germania was added to the zirconia powder so that the germania content was 0.25 mass%.

[0083] The zirconia sintered body of this example was obtained in the same manner as in Example 1, except that the sintering temperature was 1200°C.

[0084] Example 4 Zirconia powder and pure water were mixed to form a slurry in the same manner as in Example 1, and then this was spray-granulated to form a granular powder. The average granule diameter of the zirconia granules was 55 μm and the light bulk density was 1.29 g / cm. 3 It was.

[0085] A zirconia sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia granules were used.

[0086] Example 5 The zirconia powder of this example was obtained in the same manner as in Example 1, except that yttrium chloride was added to the zirconia sol so that the yttria concentration was 10 mol%, that alumina sol was added to the zirconia powder after washing with pure water so that the alumina content was 0.25 mass%, and that the zirconia powder was pre-fired at 970°C for 2 hours in air.

[0087] The zirconia sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used and the sintering temperature was 1250°C.

[0088] Comparative Example 1 A 0.37 mol / L aqueous solution of zirconium oxychloride was hydrolyzed at boiling temperature for 160 hours with stirring to obtain a zirconia sol with an adsorbed zirconium content of 12 mass% and an average sol particle size of 0.1 μm.

[0089] Yttrium chloride was added to and mixed with the zirconia sol so that the yttria concentration was 8 mol %, and the sol was dried at 160° C. in air, and then calcined at 1,030° C. for 2 hours in air to obtain zirconia powder.

[0090] The obtained zirconia powder was washed with a sufficient amount of pure water, and then made into a slurry, which was then pulverized for 30 hours in a vibration mill equipped with zirconia balls having a diameter of 10 mm as a pulverizing medium. After pulverization, the zirconia powder was dried in the air at 130° C. to obtain the zirconia powder of this comparative example.

[0091] The zirconia powder of this comparative example was molded under a pressure of 70 MPa and then sintered under atmospheric pressure at 1300° C. for 2 hours to obtain a zirconia sintered body of this comparative example.

[0092] Comparative Example 2 A zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that yttrium chloride was added to the zirconia sol so that the yttria concentration was 4 mol %.

[0093] A zirconia sintered body was obtained in the same manner as in Example 1, except that the sintering temperature was 1,350°C.

[0094] Comparative Example 3 A zirconia sol was obtained in the same manner as in Example 1. The obtained zirconia sol was washed with a sufficient amount of water, and the obtained zirconia sol had an adsorbed zirconium amount of 0.5 mass % and an average sol particle size of 0.1 μm.

[0095] Yttrium chloride was added to and mixed with the zirconia sol so that the yttria concentration was 8 mol %, and the sol was dried at 160° C. in air, and then calcined at 990° C. for 2 hours in air to obtain zirconia powder.

[0096] The obtained zirconia powder was washed with a sufficient amount of pure water, and then made into a slurry, which was then pulverized for 24 hours in a vibration mill equipped with zirconia balls having a diameter of 10 mm as a pulverizing medium. After pulverization, the zirconia powder was dried in air at 130° C. to obtain the zirconia powder of this comparative example.

[0097] A zirconia sintered body was obtained in the same manner as in Example 1, except that the sintering temperature was 1,350°C.

[0098] The evaluation results of the zirconia powders obtained in the examples and comparative examples are shown in the table below. All of the zirconia powders in the examples had a particle size peak with a peak top at 0.3 to 0.5 μm in the volume particle size distribution, and the width of the particle size peak was 0.1 μm. It was also confirmed that Comparative Example 1 had an average particle size exceeding 0.5 μm and a particle ratio of 80% or less, and Comparative Examples 2 and 3 had a monoclinic fraction of 1% or more.

[0099] [Table 1]

[0100] The evaluation results of the zirconia sintered bodies obtained in the Examples and Comparative Examples are shown in the table below. Although the zirconia sintered bodies of the Examples and Comparative Example 1 were both obtained by low-temperature sintering at 1300°C or less, the zirconia sintered body of Comparative Example 1 had a conductivity of 5.0×10 at 600°C. -3 The zirconia sintered body of the embodiment has a conductivity of 8.0×10 S / cm. -3It can be confirmed that the material has high electrical conductivity of more than S / cm.

[0101] Furthermore, the zirconia sintered bodies of Comparative Examples 2 and 3 were sintered at a relatively high temperature of 1350°C, but had an electrical conductivity of 5.0 × 10 -3 It can be confirmed that the electrical conductivity is low, at less than S / cm.

[0102] The measured density of the compact of Comparative Example 1 was 2.55 g / cm 3 In contrast, the measured density of the compacts of Examples 1 and 5, which had the same composition, was 2.76 g / cm 3 It can be confirmed that these zirconia powders exhibit high moldability.

[0103] [Table 2]

Claims

1. Contains 6 mol% or more and 10 mol% or less of yttria and has a measured density of 5.76 g / cm 3 6.01g / cm or more 3 and the electrical conductivity at 600° C. is 5.0×10 or less. -3 A zirconia sintered body having a three-point bending strength measured in accordance with JIS R 1601 of 353 MPa or more and 600 MPa or less.

2. The zirconia sintered body according to claim 1, wherein the crystal phase contains at least cubic crystals.

3. Alumina (Al 2 O 3 ), silica (SiO 2 ) and Germanium (Ge 2 O 3 The zirconia sintered body according to claim 1 or 2, comprising one or more selected from the group consisting of:

4. The zirconia sintered body according to any one of claims 1 to 3, which is for use as a solid electrolyte.

5. A solid electrolyte comprising the zirconia sintered body according to any one of claims 1 to 4.

6. A method for producing a solid electrolyte, comprising using the zirconia sintered body according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Stabilized zirconia solid electrolyte and production thereof

    JP1992012058A

  • Zirconia particle for solid electrolyte and its production

    JP1998139436A

  • High density yttria-stabilized zirconia sintered body and production method therefor

    JP2002255642A

  • High conductivity zirconia-based sintered compact

    JP2006256924A

  • Anode support substrate and anode support type cell

    JP2015187962A